If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -12 = 10 + 5x Reorder the terms: -12 + -6x = 10 + 5x Solving -12 + -6x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + -6x + -5x = 10 + 5x + -5x Combine like terms: -6x + -5x = -11x -12 + -11x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + -11x = 10 + 0 -12 + -11x = 10 Add '12' to each side of the equation. -12 + 12 + -11x = 10 + 12 Combine like terms: -12 + 12 = 0 0 + -11x = 10 + 12 -11x = 10 + 12 Combine like terms: 10 + 12 = 22 -11x = 22 Divide each side by '-11'. x = -2 Simplifying x = -2
| s(t)=-t^3+13t^2-40t | | 3c+4=11c | | -18=3(-a+6)+2z | | (7x^2-8)+(3x^2+1)= | | 13-4z=2z+9 | | 2x+2=-3x+6 | | 2x+2=4x+-6 | | cos(7x+ln(5x))=0 | | lx^2+3x+1l=1 | | 9-3x+2=10-3x | | 20+0.07(x-20)=0.06x | | 3u^2+3v^2-6uv+20u-20v+12=0 | | 1x-3y=14 | | Xy-4x+10=0 | | 9x+11=5x+1 | | 20+0.07x=0.06x | | x+9+2x=30 | | 11+2a=14 | | 3p=60+8p | | .2(x+100)=10 | | (-12)+6/2= | | 59-6x=3x+16 | | 20x+50b=320 | | -3x-y=17 | | 120+12x=545 | | 9x-2-4x-13=30 | | 4x^2-100x+625=0 | | x^2+20x+225=0 | | 4x-1=15x+1 | | 7x-6=58 | | 6x+29=Y | | x-16=-35 |